Penggunaan kontrasepsi implan 2 batang selama 1 tahun - Muhammad Dezarino; Teuku Muhammad Ichsan; Muhammad Oky Prabudi (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Background : Indonesia is a country with the largest subdermal dermal implant hormonal contraception acceptors. It is a necessity to obtain the continuation rate, side effects and effectivity data of the method.Objective : To assess the continuation rate, side effects and effectivity of 2 rods subdermal implant hormonal contraception for 1 year.Methods : A prospective designed descriptive study, from July of 2011 until July of 2012 of 150 women who accept the method. The continuation rate, side effects and effectivity of the method is recorded as data.Results : The continuation rate is as high as 94 % with menstrual disorders as the most common side effect which also the largest reason for discontinuation (55 %). Using the 3 months reference periode, the menstrual patterns are : irregular menstrual cycles (40.26-59.45%) , amenorrhea (27.02-39.01%), and normal cycles (13.51-28.85%), respectively. The method's effectivity is high, as no pregnancy were found among subjects.Conclusion: High continuation rate and effectivity, along with good tolerability related to the side effects which no serious adverse events found, suggesting the method is a feasible contraception choice.Keywords : contraception; 2 rod implants; continuation rate; effectivity; side effects; menstrual pattern